Prevalence of undiagnosed axial spondyloarthritis in inflammatory bowel disease patients with chronic back pain: secondary care cross-sectional study. (22nd August 2022) - Lim, Chong Seng Edwin; Tremelling, Mark; Hamilton, Louise; Kim, Matthew; Macgregor, Alexander; Turmezei, Tom; Gaffney, Karl
Abstract: Objective: To elucidate the prevalence of undiagnosed rheumatology-verified diagnosis of axial spondyloarthritis (RVD-axSpA) in patients attending routine secondary care IBD clinics with chronic back pain. Methods: Screening questionnaires were sent to consecutive patients attending IBD clinics in a university teaching hospital. Patients fulling the eligibility criteria (gastroenterologist-verified diagnosis, 18–80 years old, biologic therapy naive, no previous diagnosis of axSpA); and a moderate diagnostic probability of axSpA [self-reported chronic back pain (CBP) >3 months, onset <45 years] were invited for rheumatology assessment. This included medical review, physical examination, patient reported outcome measures, human leucocyte antigen B27, C-reactive protein, pelvic radiograph and axSpA protocol magnetic resonance imaging. A diagnosis of RVD-axSpA was made by a panel of rheumatologists. Results: Of the 470 patients approached, 91 had self-reported CBP >3 months, onset <45 years, of whom 82 were eligible for clinical assessment. The prevalence of undiagnosed RVD-axSpA in patients attending IBD clinics in a secondary care setting, with self-reported CBP, onset <45 years is estimated at 5% (95% CI 1.3, 12.0) with a mean symptom duration of 12 (s .d . 12.4) years. Conclusion: There is a significant hidden disease burden of axSpA among IBD patients. Appropriate identification and referral from gastroenterology is needed to potentially shorten the delay to diagnosis and allow access to appropriate therapy.